74‐1: Image Restoration for Display‐Integrated Camera. Issue 1 (25th September 2020) - Lim, Sehoon; Zhou, Yuqian; Emerton, Neil; Large, Tim; Bathiche, Steven
Abstract : Under‐display camera is of great interest in the display industry potentially eliminating the display bezel and camera notch/hole in mobile devices. However, display panels cause complex signal modulation in the camera aperture which results in obscuration, attenuation and diffraction of the incident light. We propose a learning‐based image restoration approach to enable a camera to operate underneath the display without affecting the display contrast and color gamut.